Mortality from sudden unexpected death in epilepsy (SUDEP) in a cohort of adults with intellectual disability. (7th May 2013) - Kiani, R.; Tyrer, F.; Jesu, A.; Bhaumik, S.; Gangavati, S.; Walker, G.; Kazmi, S.; Barrett, M.
Abstract Background People with intellectual disability (ID) and epilepsy are more likely to die prematurely than the general population. A significant number of deaths in people with epilepsy may be potentially preventable through better seizure control, regular monitoring and raising awareness among patients and carers. The aim of this project was to study mortality from sudden unexpected death in epilepsy (SUDEP) in adults with ID. Methods All adults (≥20 years old) living in Leicester city, Leicestershire and Rutland, UK, with ID between 1993 and 2010 were identified using the Leicestershire Intellectual Disability Register database. People with and without ID who died during the same period were identified using death certificate data from the Office for National Statistics (ONS). Deaths from probable and definite SUDEP were identified. Additional information on adults with ID who had died from probable or definite SUDEP was obtained from case notes and post‐mortem reports, where available. Cases of probable and definite SUDEP in adults with ID were compared with the general population using standardised mortality ratios (SMRs). Results A total of 898 adults with ID had died over the 18‐year study period. Of these, 244 deaths (27%) occurred in people with ID who had a diagnosis of epilepsy. Twenty‐six people with ID died from probable or definite SUDEP, which was the second most common cause of death among adults with ID and epilepsy. All‐cause specific SMRs were 2.2 [95% confidence interval (CI): 2.0–2.4] and 2.8 (95% CI: 2.5–3.1) for men and women with ID respectively. SMRs were 3.2 (95% CI: 2.7–3.8) and 5.6 (95% CI: 4.6–6.7) for men and women with epilepsy and ID respectively. During the same study period, 83 adults without ID had died of probable or definite SUDEP. The SMRs for SUDEP in patients with ID were 37.6 for men (95% CI: 21.9–60.2) and 52.0 for women (95% CI: 23.8–98.8). We found that in the majority of ID cases there was little detailed documentation on the circumstances surrounding deaths, no communication with patients/carers about risk of SUDEP and an absence of post‐mortem reports or carers' referral for bereavement counselling. Conclusion The authors believe that a comprehensive risk management under a multiagency/multidisciplinary framework should be undertaken for all adults with ID and epilepsy in day‐to‐day clinical practice to reduce mortality in people with ID.